Effect Type of Desorption Eluent and Concentration in Desorption of Zn2+ Cation from Sulfonate Modified Silica Gel-GPTMS (Glycydoxypropyltrimethoxysilane) Adsorbent - Hafis, Muhamad; Oktavia, Budhi; Alizar, Alizar; Warda Ningsih, Sherly Kasuma (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Silica has silanol groups contained in it which have low binding ability because it has low acidity, resulting in low absorption effectiveness on silica. In order to improve the properties and to expand the field of utilization, a modification process is carried out on silica gel using GPTMS bridging compounds and sulfonate salts as modifiers. The study explains that CaCl2.2H2O with a desorption percent of 97.25% has a greater ability than NaCl which is only 83.93% in the desorption of Zn2+ cations. The study also explains that the optimum concentration of CaCl2.2H2O eluent in the desorption of Zn2+ cations is at 1mmol/L where the desorption yield is 93.74%.